Guatemala : Selected Issues and Analytical Notes. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper estimates both Guatemala's potential output and output gap using a wide range of econometric techniques. The analysis suggests that Guatemala's potential output growth is about 3.5 percent for the whole sample period and that the output gap is almost closed. Results are highly robust among different methodologies. Among the methods used, several well-known time series filters and two different estimations of a state-space model are included. Additionally, a test for structural breaks in the series of potential GDP is presented. All methodologies conclude that the output gap at the end of 2012 is almost closed at -0.2 percent of potential GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet